2010
DOI: 10.1111/j.1741-6787.2009.00168.x
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Evidence-Based Practice in Nursing Using Action Research: A Review

Abstract: A B S T R A C T Background:As is often reported in the literature exploring the research-practice gap, applying the principles of evidence-based practice is easier said than done. Action research is a methodology with an explicit intent of linking the worlds of research and practice. This review attempts to answer the question: What is known about implementing evidence-based practice in nursing through action research?Approach: A total of 21 action research studies have been used to answer this question. To pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
84
0
13

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(100 citation statements)
references
References 48 publications
3
84
0
13
Order By: Relevance
“…Insofar as investigators may use, for instance, workplace learning in CIPE but neglect to spell it out in their publications, they inhibit knowledge sharing and the transferability of their findings. This failure is thus as significant a methodological shortcoming as conducting PAR cyclical process blindly (Badger, 2000;Hope & Waterman, 2003;Munten et al, 2010;Waterman et al, 2001).…”
Section: Methodological and Philosophical Shortcomingsmentioning
confidence: 95%
See 3 more Smart Citations
“…Insofar as investigators may use, for instance, workplace learning in CIPE but neglect to spell it out in their publications, they inhibit knowledge sharing and the transferability of their findings. This failure is thus as significant a methodological shortcoming as conducting PAR cyclical process blindly (Badger, 2000;Hope & Waterman, 2003;Munten et al, 2010;Waterman et al, 2001).…”
Section: Methodological and Philosophical Shortcomingsmentioning
confidence: 95%
“…It is also astonishing to discover that many authors do not describe the conduct of their PAR cyclical process (Hope & Waterman, 2003;Munten et al, 2010). PAR co-participants apparently proceed as best they can to decide on the conduct, frequency and length of their meetings with often hit-and-miss and suboptimal results (Hope & Waterman, 2003;Munten et al, 2010).…”
Section: Methodological and Philosophical Shortcomingsmentioning
confidence: 95%
See 2 more Smart Citations
“…For the clinical settings, ten Ham [1] integrate reviewed 35 documents regarding the characteristics of benefit levers' for evidences-based nursing practices and indicated that three standards of individual, organizational, and contextual trait were merged into the different types, strategies, position, attitude, and support of leadership for the purpose of changing by the reinforcing structures. However, Munten [2] integrated reviewed 21 action studies to identify the lack of implementation strategies in terms of the intensity and frequency so that the authors could not provide evidences-based protocols for nursing research using action designed; additionally, the majority of research projects were focus on improving the knowledge of nurses, but their performances and the patients' outcomes. Therefore, Wright [3] integrate reviewed 18 articles following 85 unique resources regarding the productive ward of releasing time to care for the patients and identified seven themes were focused on the direct care time of the patient and staff experience emphasizing on the major issues of patient safety and financial impact as well as the team cooperation and support of leadership playing the success and barriers of determinants.…”
mentioning
confidence: 99%